Direct detection of resistance to fluoroquinolones/SLIDs in sputum specimen by GenoType MTBDRsl v.2.0 assay A study from Eastern Uttar Pradesh, India - Kamal Singh; Richa Kumari; Smita Gupta; Rajneesh Tripathi; Anjali Srivastava; Vidisha Shakya; Ankush Gupta; Shampa Anupurba (BMC, 2021)
Abstract Background According to World Health Organization (WHO), drug-resistant tuberculosis (DR-TB) is a major contributor to antimicrobial resistance globally and continues to be a public health threat. Annually, about half a million people fall ill with DR-TB globally. The gradual increase in resistance to fluoroquinolones (FQs) and second-line injectable drugs (SLIDs), poses a serious threat to effective TB control and adequate patient management. Therefore, WHO suggests the use of GenoType MTBDRsl v.2.0 assay for detection of multiple mutations associated with FQs and SLIDs. Hence, the study was conducted to determine the prevalence of resistance to FQs and SLIDs by comparing direct GenoType MTBDRsl v.2.0 assay with phenotypic drug susceptibility testing (DST). Methods The study was conducted on 1320 smear positive sputum samples from a total of 2536 RR-TB, confirmed by GeneXpert MTB/RIF. The smear positive specimens were decontaminated, and DNA extraction was performed. Furthermore, the extracted DNA was used for GenoType MTBDRsl v.2.0 assay. While 20% of the decontaminated specimens were inoculated in Mycobacterium growth indicator tube (MGIT) for drug susceptibility testing (DST). Results Out of 1320 smear positive sputum samples, 1178 were identified as Mycobacterium tuberculosis complex (MTBC) and remaining were negative by GenoType MTBDRsl v.2.0 assay. Of the 1178 MTBC positive, 26.6% were sensitive to both FQs and SLIDs, whereas 57.3% were only FQs resistant and 15.9% were resistant to both FQs and SLIDs. Further DST of 225 isolates by liquid culture showed that 17% were sensitive to both FQs and SLIDs, 61.3% were only FQs resistant and 21.3% were resistant to both. The specificity for FQs and SLIDs was 92.31% and 100% whereas sensitivity was 100% respectively by GenoType MTBDRsl v.2.0 assay in direct sputum samples. Conclusions Our study clearly suggests that GenoType MTBDRsl v.2.0 assay is a reliable test for the rapid detection of resistance to second-line drugs after confirmation by GeneXpert MTB/RIF assay for RR-TB. Though, high rate FQ (ofloxacin) resistance was seen in our setting, moxifloxacin could be used as treatment option owing to very low resistance.